The impact of different language policies to teach maths and science on language choices of UiTM Sarawak's diploma in science students / Caesar Dealwis … [et.al.]. - Dealwis, Caesar; Johari, Aiza; Botley @Faizal Hakim, Simon (2011)
This sociolinguistic study focuses on the younger generation of multilingual Malaysian tertiary students who have been exposed to different mediums of instruction when studying Science and Mathematics at school before joining UiTM. This study is limited to two domains, namely friendship and study, because these are the domains where the impact of the different language policies could be more obvious in influencing the language choices of the students,